2022
DOI: 10.1186/s12877-022-02891-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic vulnerability and frailty among community-dwelling older adults: cross-sectional findings from longitudinal aging study in India, 2017–18

Abstract: Introduction The Indian population is rapidly aging with huge proportion of illiterate and socioeconomically disadvantaged people and there is a dearth of research on the relationships between factors of socioeconomic vulnerability and frailty in older people. The present study examined the cross-sectional associations between socioeconomic vulnerability and physical frailty in community-dwelling older individuals in India. Materials and methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 69 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, research showed that a low SES is associated with more disadvantages and increased chronic illnesses and functional disabilities [20][21][22]. A recent study among older Indian adults suggested that socioeconomic disadvantages are positively associated with old age physical frailty [23]. On the other hand, a higher SES was found to be negatively associated with physical disability, frailty and mortality [24,25].…”
Section: Relationship Between Ses Functional Independence and Social ...mentioning
confidence: 99%
“…Furthermore, research showed that a low SES is associated with more disadvantages and increased chronic illnesses and functional disabilities [20][21][22]. A recent study among older Indian adults suggested that socioeconomic disadvantages are positively associated with old age physical frailty [23]. On the other hand, a higher SES was found to be negatively associated with physical disability, frailty and mortality [24,25].…”
Section: Relationship Between Ses Functional Independence and Social ...mentioning
confidence: 99%
“…They also highlighted that the gap between the gender-specific prevalence of frailty syndrome was wider for India. The national prevalence of physical frailty for males was 27.4% and 32.2% for females according to the Longitudinal Aging Study in India (LASI), 2017–2018 [ 6 ]. In India, the aging population is a socially unequal and heterogeneous section with a male and female divide.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies from India have reported frailty in hospital and community settings [5][6][7][8]. Few studies from India have recently reported on IC as well [9,10].…”
Section: Introductionmentioning
confidence: 99%